(untitled) (Applied Biological Research, 2012)
The present study was conducted on thirty apparently healthy adult yaks of either sex reared under traditional migratory free range system of rearing. Blood samples were analyzed for normal hematology, serum biochemical parameters and micro-mineral status of yaks when grazed in summer grazing ground and winter grazing ground. Hemoglobin content in yaks in summer grazing grounds was significantly (P0.01) higher than that of animals in winter pastures. Red blood corpuscle (RBC) counts, white blood cell (WBC) counts, erythrocytic sedimentation rate (ESR) and packed cell volume (PCV) in yaks were similar in both summer and winter pasture. Similarly, no significant difference was observed in any of the biochemical parameters studied. The mean cobalt and zinc values in blood were significantly higher in animals grazing in summer grazing ground than those in winter grazing ground. However, the mean copper value was lower than the critical value indicating possible Cu deficiency.